Cell-cell interactions in synovitis: Interactions between T lymphocytes and synovial cells - McInnes, Iain B (BioMed Central, 2000)
Mechanisms whereby T lymphocytes contribute to synovial inflammation in rheumatoid arthritis are poorly understood. Here we review data that indicate an important role for cell contact between synovial T cells, adjacent macrophages and fibroblast-like synoviocytes (FLS). Thus, T cells activated by cytokines, endothelial transmigration, extracellular matrix or by auto-antigens can promote cytokine, particularly TNFα, metalloproteinase production by macrophages and FLS through cell-membrane interactions, mediated at least through β-integrins and membrane cytokines. Since soluble factors thus induced may in turn contribute directly to T cell activation, positive feedback loops are likely to be created. These novel pathways represent exciting potential therapeutic targets.